Study of Efficacy and Safety of Triple Combination Agent (4% Hydroquinone, 0.05% Tretinoin and 0.05% Clobetasone Butyrate) in the Treatment of Melasma (Faridpur Medical College Journal, 2013)
Melasma is a very common disorder of hypermelanosis affecting face. The pigmented patches usually affect darker complexioned individual especially Asian. An interventional study was carried out to detect the efficacy and safety of triple combination agent (4% Hydroquinone, 0.05% Tretinoin and 0.05% Clobetasone butyrate) in the treatment of melasma. Total 50 clinically diagnosed cases of melasma attending in outpatient department of Dermatology and Venereology, Diabetic Association Medical College Hospital (DAMCH), Faridpur were evaluated. Maximum patients (40%) were between 31-35 years of age and 80% were female. Sun exposure (60%) and contraceptive pill (36%) were common precipitating factors. Of them 54% patients have skin type IV, 24% patients have skin type III. Centrofacial melasma (64%) was the commonest pattern of melasma. MASI score at base line was 9.45, and after 12th week were 4.62. After completion of therapy there was remarkable reduction (51.11%) of severity of melasma. The triple combination agent were well tolerated and commonly observed side effects were erythema (34%) and burning (22%). This study demonstrates that every night application of triple combination agents has significant lightening effect in the treatment of melasma.a DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16893 Faridpur Med. Coll. J. 2013;8(1): 22-25